Dimensional analyses and surface quality of the laser cutting process for engineering plastics - DEMİRER, HALİL; KURT, MUSTAFA; KAYNAK, YUSUF (SPRINGER LONDON LTD, 2009)
In this study, the effect of the CO2 laser cutting process parameters (gas pressure, cutting speed, and laser power) on the dimensional accuracy and measured surface roughness of engineering plastic (PTFE and POM) materials was investigated. Cutting surface profile of specimens was examined by using an optical microscope. The surface quality of specimens was examined by measuring surface roughness and form error. Analysis of variance (ANOVA) and regression analyses are employed to assess the effect of the process parameters on the dimensional accuracy.
Keywords: Laser cutting; Analysis of variance (ANOVA); Engineering plastics; Dimensional error; CO2-LASER; OPTIMIZATION